Prenatal ultrasonographic features in Blomstrand osteochondrodysplasia: Antenatal case series confirmed by postmortem radiology and molecular diagnosis. (20th July 2022) - Sarac Sivrikoz, Tugba; Kalayci, Tugba; Senturk, Leyli; Karaman, Volkan; Kalelioglu, Ibrahim Halil; Has, Recep; Kayserili, Hulya; Uyguner, Zehra Oya; Nishimura, Gen; Altunoglu, Umut
Abstract: Objective: Blomstrand osteochondrodysplasia (BOCD, MIM #215045) is an ultrarare lethal skeletal dysplasia (LSD) perinatally, characterized by extremely advanced bone maturation, generalized osteosclerosis, and severe tetramicromelia caused by biallelic loss‐of‐function mutations in the parathyroid hormone receptor‐1 gene ( PTHR1 ). We aim to describe prenatal ultrasonographic features in a retrospective fetal case series of BOCD and emphasize the importance of multidisciplinary antenatal evaluation of LSDs to improve the differential diagnosis. Method: Prenatal ultrasound findings of five fetal cases diagnosed with BOCD between 2000 and 2019 in the Prenatal Diagnosis Unit and Medical Genetics were reviewed, along with postmortem examination results and confirmatory molecular results. Results: All fetuses presented with severe sonographic findings of LSDs comprising tetramicromelia, thoracic hypoplasia, and retro‐micrognathia. Marked cervical hyperextension was present in three fetuses. Flared metaphyses were prenatally identified in only one fetus. X‐rays of four fetuses evaluated postmortem showed advanced bone maturation, generalized osteosclerosis, and dumbbell‐like appearance of long bones due to metaphyseal enlargement. Conclusion: The presence of retro‐micrognathia along with a protruding tongue and severe metaphyseal flaring can suggest a diagnosis of BOCD, when prenatal ultrasound findings are indicative for LSD. The diagnosis can be ascertained through postmortem clinical and radiological evaluation and/or molecular testing. Key points: What's already known about this topic? Postmortem radiologic diagnosis of Blomstrand osteochondrodysplasia (BOCD) has been well characterized. However, no specific antenatal ultrasound finding has been implemented in the diagnosis of this ultrarare skeletal dysplasia, except for severe tetramicromelia. What does this study add? It's emphasized that severe retro‐micrognathia may be a remarkable feature, in addition to previously well‐documented prenatal findings in BOCD. Meticulous prenatal ultrasound evaluation is required for the detection of flaring of metaphyses. Other ultrasound findings are proptosis, cervical hyperextension, and kyphoscoliosis.